Recent advances on mixed metal sulfides for advanced sodium-ion batteries - Fang, Yongjin (2021)
Sodium-ion batteries (SIBs) have drawn enormous attention in the past few years from both academic and industrial battery communities in view of the fascinating advantages of rich abundance and low cost of sodium resources. Among various electrode materials, mixed metal sulfides (MMSs) stand out as promising negative electrode materials for SIBs considering their superior structural and compositional advantages, such as decent electrochemical reversibility, high electronic conductivity, and rich redox reactions. Here, a summary of some recent developments in the rational design and synthesis of various kinds of MMSs with tailorable architectures, structural/compositional complexity, controllable morphologies, and enhanced electrochemical properties is presented. The effect of structural engineering and compositional design of MMSs on the sodium storage properties is highlighted. It is anticipated that further innovative works on the material design of advanced electrodes for batteries can be inspired.